The Emerging Crisis of Aged Homelessness in the US: Could Cost Avoidance in Health Care Fund Housing Solutions? - Culhane, Dennis; Doran, Kelly; Schretzman, Maryann; Johns, Eileen; Treglia, Daniela; Byrne, Thomas; Metraux, Stephen; Kuhn, Randall (International Journal of Population Data Science, 2019)
Background with rationale The US homeless population has had a fairly unique age structure for thirty years, with one-third concentrated among the 1955-1965 birth cohort. They are aging prematurely and are experiencing aging related morbidity and mortality in increasing numbers. This study uses demographic methods to project the growth in aged homelessness out to 2030. Using linked administrative data, historical patterns of health care, nursing home and shelter are used to estimate future costs. Potential offsets are estimated from anticipated reductions in excess services use associated with housing placement. Main Aim To determine if housing placement among future aged homeless adults could be offset by reduced health and social service costs. Methods/Approach Demographic methods are applied to historical shelter data in Los Angeles, New York and Boston to project the future growth in aged homelessness. Linked administrative data are used to estimate future age-related use of health and social services. Housing models are applied to meet population needs to estimate costs. Health and social service costs offsets are estimated from prior literature. The net cost is estimated based on the differential. Results Elderly homelessness will triple in the US over the next ten years. Average annual health and shelter costs will be $22-28,000 per person. Housing costs are estimated at $7-11,000 annually. Cost offsets yield a positive ROI of 1.13 in New York and Los Angeles; Boston results are closer to break-even. Conclusion Substantial public dollars will be spent on the aged homelessness problem as it triples over the next ten years. Some of those dollars could be shifted to housing solutions, reducing homelessness significantly, with little to no increase in public expenditures; positive returns on such investments are also possible.